Pengaruh Pemberian Kapur Dolomit dan Pupuk Urea terhadap Emisi Gas Metana (CH4) pada Tanaman Padi (Oryza sativa L.) di Tanah Gambut - Prayitno, Muh Bambang; Purnomo Aji, Arif (Seminar Nasional Lahan Suboptimal, 2021)
Prayitno MB, Aji AP. 2021. Influence of dolomite lime and urea fertilizer on methan (CH4) emissions in rice plants (Oryza Sativa L.) on peat soil. In: Herlinda S et al. (Eds). Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021, Palembang 20 Oktober 2021. pp. 682-688. Penerbit: Penerbit dan Percetakan Universitas Sriwijaya (UNSRI).This study aims to see how the effect of dolomite lime and urea fertilizer for different doses on methane emissions in peat soils in rice plants. CH4 gas analysis was carried out at the Agricultural Environmental Research Laboratory, Ministry of Agriculture, Pati, Central Java. Gas extraction and gas analysis were carried out from March to June 2020. The main production observation variables observed in this study were CH4 methane emissions during the vegetative, primordial, generative and. The supporting parameters include water pH and water EC. The results of this study indicate that the dynamics of CH4 gas emission varies greatly in each phase. In the observations in the vegetative phase, plants treated with D2U1 with a value of 4,69 mg/m2/day were the lowest CH4 gas emissions, while in the primordial phase plants treated with D1U1 had the lowest CH4 gas emissions with a value of 5,58 mg/ m2/day. In the generative phase of plants with D2U1 treatment with a value of 5,10 mg/m2/day is the lowest CH4 gas emissions and in the production phase with D2U2 treatment produces the lowest CH4 emissions with a value of 4,78 mg/m2/day. Based on during the growth phase, the lowest CH4 emissions produced in the D2U1 treatment were in the vegetative phase with a value of 4,69 mg/m2/day.